Salinity effects on cultured Neogloboquadrina pachyderma (sinistral) from high latitudes: new paleoenvironmental insights - Bertlich, Jacqueline; Gussone, Nikolaus; Berndt, Jasper; Arlinghaus, Heinrich F.; Dieckmann, Gerhard S. (Geo-Marine Letters, 2021)
This study presents culture experiments of the cold water species Neogloboquadrina pachyderma (sinistral) and provides new insights into the incorporation of elements in foraminiferal calcite of common and newly established proxies for paleoenvironmental applications (shell Mg/Ca, Sr/Ca and Na/Ca). Specimens were collected from sea ice during the austral winter in the Antarctic Weddell Sea and subsequently cultured at different salinities and a constant temperature. Incorporation of the fluorescent dye calcein showed new chamber formation in the culture at salinities of 30, 31, and 69. Cultured foraminifers at salinities of 46 to 83 only revealed chamber wall thickening, indicated by the fluorescence of the whole shell. Signs of reproduction and the associated gametogenic calcite were not observed in any of the culture experiments. Trace element analyses were performed using an electron microprobe, which revealed increased shell Mg/Ca, Sr/Ca, and Na/Ca values at higher salinities, with Mg/Ca showing the lowest sensitivity to salinity changes. This study enhances the knowledge about unusually high element concentrations in foraminifera shells from high latitudes. Neogloboquadrina pachyderma appears to be able to calcify in the Antarctic sea ice within brine channels, which have low temperatures and exceptionally high salinities due to ongoing sea ice formation.